2023
DOI: 10.7759/cureus.45461
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rheumatologist in Smoking Cessation of Ankylosing Spondylitis Patients: A Single-Center Cross-Sectional Study

Mehmet Nur Kaya,
Seda Yurumez,
Emre Tekgöz
et al.

Abstract: Objectives: Smoking has a well-established detrimental effect on the prognosis and treatment success in patients with ankylosing spondylitis. It is important to encourage and convince patients to quit smoking. We aimed to evaluate the contribution of rheumatologists to smoking cessation in patients with ankylosing spondylitis.Methods: This single-center cross-sectional study was conducted in a tertiary research hospital between March 2022 and June 2022. The data related to demographics, smoking status, duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Considering the detrimental effects of smoking on axSpA, it is imperative to encourage and provide support for smoking cessation in all patients with this condition. Several studies have demonstrated that physicians' advice to quit smoking serves as a strong motivator to pursue smoking cessation (smoking cessation rate: 3% vs. 6%) [11].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Considering the detrimental effects of smoking on axSpA, it is imperative to encourage and provide support for smoking cessation in all patients with this condition. Several studies have demonstrated that physicians' advice to quit smoking serves as a strong motivator to pursue smoking cessation (smoking cessation rate: 3% vs. 6%) [11].…”
Section: Smoking Cessationmentioning
confidence: 99%